Usaha Lulur Daun Pepaya untuk Menghadapi Pandemi Covid-19 - Riski Sulistiarini; Novita Eka Kartab Putri; Fathul Jannah; Nur Shidiq; Kasdi Kasdi; Yuni Fardalianna; Gayuk Kalih Prasesti (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
The purpose of this community service activity is as a form to improve the community's economy during the COVID-19 pandemic by utilizing waste from papaya leaves. With this training in making scrubs, it is hoped that it can increase creativity and public awareness of the potential for waste around to be used as business opportunities, especially during this COVID-19 pandemic. Currently commercially available cosmetic formulations (exfoliants) for topical use are alpha hydroxy acids, beta hydroxy acids and retinoids, which can cause adverse reactions. Therefore, it is necessary to use cosmetic ingredients consisting of effective and non-irritating exfoliants, one of which is the use of papaya leaves which are formulated as scrubs. The target of this activity is the residents of Mugirejo Village, Samarinda, East Kalimantan. Education and training on making scrubs went smoothly and without any problems. All residents followed the training process carefully and were very enthusiastic, as evidenced by the full attention of the residents until the end of the activity. Through representatives of community leaders, this activity is considered very useful and is expected to increase the potential for utilizing papaya leaf waste which can be used as a business opportunity.